Fabrication of Si3N4 Nanocrystals and Nanowires Using PECVD - Jingwei Song; Xiying Ma; Wang Zui; Chen Wei; Zhongpin Chen (Advances in Materials Science and Engineering)
Si3N4 nanowires and nanocrystals were prepared on Si substrates with or without Fe catalyst using silane (SiH4) and nitrogen (N2) as reactive gases through plasma-enhanced chemical vapor deposition (PECVD) technology. With Fe catalyst, Si3N4 nanowires were developed, indicating that Fe catalyst played a role for Si3N4 molecules directionally depositing into strings. The density of the nanowires is closely related to the density of Fe catalyst. When the density of Fe ions on the substrate was decreased remarkably, a smooth superlong Si3N4 nanowire with 12 μm in length was fabricated. Having analyzed the growth mechanism, a growth model for Si3N4 nanowires was developed. The growth of Si3N4 nanocrystallines was attributed to be a vapor-solid (V-S) deposition process.